Patient-reported outcomes and medical device evaluation: from conception to implementation - Christina M. Webber; Brittany Caldwell; Fraser D. Bocell; Anindita Saha; Michelle E. Tarver (Journal of Patient-Reported Outcomes, 2022)
Abstract Background The insights gleaned from patient-reported outcomes (PROs) have implications across the healthcare ecosystem, from clinical investigations to evaluate the safety and effectiveness of medical devices to clinical care and reimbursement decisions. The U.S. Food and Drug Administration’s (FDA) Center for Devices and Radiological Health (CDRH) hosted a public meeting in September 2020 discussing how PROs can be used in medical device evaluation throughout the total product life cycle, as well as methods for developing and modifying PRO instruments to ensure they are fit-for-purpose. This commentary presents key points of discussion from the meeting, providing insight into the increased interest in PRO data to support medical product development while also exploring future opportunities of incorporating PRO data throughout healthcare. Main Body. Thoughtful use of fit-for-purpose PRO instruments to integrate the patient’s voice into clinical care paradigms, medical device development, regulatory decisions, and reimbursement and coverage decisions were emphasized throughout the meeting. Existing PRO instruments may be used if the context of use is appropriate. Modifications to an existing PRO instrument may also be explored to ensure the instrument is fit-for-purpose in a new context of use. Development of a novel PRO instrument may be necessary to capture attributes in a new patient population or application. Multi-stakeholder collaborations, of which patients are a key component, create efficiencies in the development and modification of PRO instruments. Conclusion Continued multi-stakeholder collaborations bringing together researchers, clinicians, patients, regulators, and payers are critical to further advance the inclusion of the patient voice incorporating PRO instruments throughout the healthcare ecosystem in an efficient manner that is least burdensome to patients.